Literature Review: Comprehensive Diagnostic Approach to Nipah Virus Infection; Integrating Clinical Features and Laboratory Confirmation - Hidayat Hidayat; Mulat Muliasih (Universitas Malahayati, 2026)
Nipah virus (NiV) infection is a highly fatal zoonotic disease that requires rapid and accurate diagnosis to reduce mortality and prevent outbreaks. This literature review aims to summarize current evidence on a comprehensive diagnostic approach integrating clinical features and laboratory confirmation of NiV infection. A structured search was conducted using databases such as PubMed, ScienceDirect, and WHO reports, focusing on peer-reviewed articles published within the last decade. Clinically, NiV infection presents with acute febrile illness, respiratory symptoms, and encephalitis, often supported by nonspecific laboratory findings such as thrombocytopenia and elevated liver enzymes. However, definitive diagnosis relies on laboratory confirmation. Real-time reverse transcription polymerase chain reaction (RT-PCR) remains the gold standard for early detection due to its high sensitivity and ability to detect viral RNA in multiple specimen types. Serological assays, particularly ELISA, complement diagnosis by identifying IgM and IgG antibodies during different stages of infection. Virus isolation and immunohistochemistry are confirmatory but limited by biosafety constraints. Recent advances highlight the growing role of rapid molecular techniques, though their implementation remains limited. Additionally, higher viral load detected by RT-PCR is associated with severe outcomes, underscoring its prognostic value. In conclusion, integrating clinical assessment with molecular and serological methods is essential for timely and accurate diagnosis of NiV infection, while further development of accessible diagnostic tools remains a global priority.